The Predictive Model of Citizens' Attitudes About the Risks of Introducing the Death Penalty in the Serbian Criminal Justice System - Cvetković, Vladimir; Bugarski, Tatjana; Martinović, Jovana (NBP. Nauka, bezbednosti, policija, 2022)
This paper presents the results of quantitative research regarding the predictive model of citizens' attitudes about the risks of introducing the death penalty in the Serbian criminal justice system. We tested the central hypothesis of which gender is predicting variables in citizens' attitudes about the risks of introducing the death penalty in the Serbian criminal justice system. The research was conducted with the use of a questionnaire that was requested and then collected online from 427 people in June 2021. A multivariate regression analysis was used, identifying the extent to which total scores of the main dependent variables (introducing the death penalty; trust in the criminal justice system; advantages of introduction; disadvantages of introduction scores) were associated with five demographic and socio-economic variables: gender, marital, education, income, and age. The findings revealed that gender and educational level were the most effective predictors of the research variables under question. The majority of respondents support the introduction of the death penalty and the most important predictor of disadvantages of introducing the death penalty in the Serbian criminal justice system is age. Based on the findings that there are major differences in the citizens' attitudes about the risks of introducing the death penalty in the criminal justice system, policies, strategies, and regulations must take into account these very important findings. The presented model can be used for a more detailed understanding of people's attitudes regarding the support and opposition to the introduction of the death penalty in the Serbian criminal justice system.
Keywords: criminal justice; death penalty; risk assessment; prediction; decision making.